Interrelationship of Millennial Generation Leadership Style Indicators at PLN Central Java & DIY Distribution Main Unit Using Interpretive Structural Modeling (ISM) Approach - Muhdam Azhar; Mahfudz Mahfudz (OPSI, 2021)
Manager at PT. PLN Persero has an important role in balancing internal relations with employees and external parties such as stakeholders. PT. PLN (Persero) Distribution Central Java and Yogyakarta D.I consists of a Unit Pelaksana Pelayanan Pelanggan (UP3) and Unit Layanan Pelanggan (ULP), ULP is directly related to the community and stakeholders. ULP Managers consists of Millennial Generation is 87% and Generation X 13%. The generation gap between Generation X and Generation Y (millennials) caused by the 7 years vacuum of recruitment, it causes of communication problems and Generation Y rapid adaptation to become young managers. Indicators identification are needed related to Generation Y's leadership style so that young managers are better prepared. Identification of the relationship between indicators is carried out using the Interpretive Structural Modeling (ISM) method and then classifying indicators using the Multiplication Applied to a Classification (MICMAC) method. There are 7 indicators obtained from ISM: M1 (Communication Method), M2 (Media Communication), M3 (Managing Team Involvement), M4 (Resolving Internal Conflicts), M5 (Risk Management), M6 (Responding to Change), M7 (Managing Stakeholder). MICMAC analysis results are M7 in the Dependent Indicators Cluster, the other indicators from M1, M2, M3, M4, M5, M6 are in the Linkage Indicators Cluster.